2022
DOI: 10.3390/life12121951
|View full text |Cite
|
Sign up to set email alerts
|

The Dosage Effect of Laser Acupuncture at PC6 (Neiguan) on Heart Rate Variability: A Pilot Study

Abstract: Laser acupuncture (LA) has been more applicated in the clinical practice with good responses, but the dosage and parameter settings are still inconsistent with the arguments. This study is focused on the effect of LA on heart rate variability (HRV) with different energy density (ED). Based on the Arndt–Schulz law, we hypothesized that the effective range should fall within 0.01 to 10 J/cm2 of ED, and settings above 10 J/cm2 would perform opposite or inhibitory results. We recruited healthy adults in both sexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Our study diverges from this trend by recruiting individuals from the general population and investigating the potential physiological follow-up effects resulting from stimulation of different EDs, an area that has received comparatively little attention. Our achievement is not only consistent with the usage methodology and parameter settings recommended by prior related journals ( Huang et al, 2009 ; Zein et al, 2018 ; Cronshaw et al, 2019 ; Chang et al, 2022 ), but also carries implications for the safety of LA application and the varying biological effects resulting from distinct dosages. Our findings provided a valuable foundation and reference for operators and researchers in developing future treatment strategies or research designs.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our study diverges from this trend by recruiting individuals from the general population and investigating the potential physiological follow-up effects resulting from stimulation of different EDs, an area that has received comparatively little attention. Our achievement is not only consistent with the usage methodology and parameter settings recommended by prior related journals ( Huang et al, 2009 ; Zein et al, 2018 ; Cronshaw et al, 2019 ; Chang et al, 2022 ), but also carries implications for the safety of LA application and the varying biological effects resulting from distinct dosages. Our findings provided a valuable foundation and reference for operators and researchers in developing future treatment strategies or research designs.…”
Section: Discussionsupporting
confidence: 79%
“…This omission is primarily due to this study’s reliance on established empirical medical research findings, and it is deemed unnecessary to reiterate the impact of RVLM on the SNS and BP. Our team’s preliminary research already exhibits that distinct EDs can produce varying degrees of impact on the ANS ( Chang et al, 2022 ), exhibiting a biphasic dose–response phenomenon. The primary aim of this study is to employ this premise as a means to investigate alterations in the FC between relevant brain regions in response to varying EDs of LA.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, the optical profile or radiation pattern of the light source is a parameter that affects the distribution of light in our tissue [ 51 ], thus affecting the efficiency of PBM. Dosage is another parameter that affects the effect of LA on adjusting the ANS [ 52 ]. The ANS may be adjusted by changing the dose on the same acupoint.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, considering the physiological perspective, within the recent publications from our team the investigations have revealed that the stimulation of the median nerve at various intensities has the capacity to modulate the parameters associated with heart rate variability (HRV) [39]. These parameters encompass the activity of the parasympathetic (PNS) and sympathetic nervous systems (SNS), and the association with CAD is also attributed to abnormal performance or heightened activity of the SNS [40].…”
Section: The Possible Linking Between Nmds and Coronary Artery Diseasesmentioning
confidence: 99%